Characterisat ion of Major Forests in Tamil Nadu based on Climate and Soil-site Characterist ics for Ident ifying Potent ial Areas for Afforestat ion - Dharumarajan, S.; Lalitha, M.; Naidu, L. G. K.; Singh, S. K. (International Journal of Bio-resource and Stress Management, 2023)
Global climate change may have an impact on forest cover. Comprehensive knowledge on soils and climatic resources helps to identify the potential areas for afforestation. The present study was aimed to assess the impact of soil and climatic resources on different existing forest types to identify the problems and potentials of forest pockets for afforestation in Tamil Nadu. The soil resource information developed by ICAR- National Bureau of Soil Survey and Land Use Planning (ICAR-NBSS and LUP), Length of Growing Period (LGP) and forest cover map of Tamil Nadu was used to evaluate the soil site characters supporting various forest types by Overlay analysis in the GIS environment. Soil site characters and climatic parameters which supporting dense, open and scrub forest were quantified and verified in the ground. The results show that soil depth and length of growing period were found to be two significant key factors influencing the forest type. Moderately deep (75 to 100 cm) to very deep (>150 cm) soils with moist period of 5 to 9 months are found suitable for dense forest cover whereas shallow depth, presence of higher proportion of gravels in sub soil and prolonged dry period are identified as major constraints in open and scrub forest. By using overlay technique, potential forest areas were identified based on soils and site characteristics for afforestation and suitable soil and water conservation measures were suggested to develop sustainable forest cover.